Evaluasi Kebijakan Infrastruktur di Indonesia: Studi Kasus pada Pembangunan Jalan Tol di Kecamatan Mojo Kediri Tulungagung - Fitra Nurhakim; Sri Lestari (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
This study aims to evaluate the toll road development policy in Mojo, Kediri, and Tulungagung sub-districts, and analyze the social, economic, and environmental impacts caused. The research method used is a qualitative approach with a case study type. The results show that toll road development has a positive impact on the local economy, especially in improving connectivity and encouraging investment in the industrial and tourism sectors. However, social impacts such as community dislocation and accessibility inequality are significant challenges. In addition, environmental impacts such as ecosystem damage and air pollution also need more attention. While this policy is effective in achieving economic objectives, post-construction toll road management and maintenance still need to be improved.